Hyperesthesias of the posterior wall of the abdomen: deep palpation Contribution to the diagnosis of visceral lesions, subacute. Chronic and acute without contraction of the abdominal wall. How this research was born - Capurro, Rafael (Cirugía del Uruguay, 2020)
Presented at session 8th April 1942